Inhibitor of Sarco/Endoplasmic Reticulum Calcium-ATPase Impairs Multiple Steps of Paramyxovirus Replication - Kumar, Naveen; Khandelwal, Nitin; Kumar, Ram; Chander, Yogesh; Rawat, Krishan Dutt; Chaubey, Kundan Kumar; Sharma, Shalini; Singh, Shoor Vir; Riyesh, Thachamvally; Tripathi, Bhupendra N.; Barua, Sanjay (Frontiers in Microbiology, 2019)
Sarco/endoplasmic reticulum calcium-ATPase (SERCA) is a membrane bound cytosolic enzyme that is known to regulate the uptake of calcium into the sarco/endoplasmic reticulum. Herein, we demonstrate for the first time that SERCA can also regulate virus replication. Treatment of Vero cells with SERCA specific inhibitor (Thapsigargin) at a concentration that is nontoxic to the cells significantly reduced Peste des petits ruminants virus (PPRV) and Newcastle disease virus (NDV) replication. Conversely, overexpression of SERCA rescued the inhibitory effect of Thapsigargin on virus replication. PPRV and NDV infection induced SERCA expression in Vero cells which could be blocked by Thapsigargin. Besides inducing enhanced formation of cytoplasmic foci, Thapsigargin was shown to block viral entry into the target cells as well as synthesis of viral proteins. Furthermore, NDV was shown to acquire significant resistance to Thapsigargin upon long-term passage (P=70) in Vero cells. As compared to the P0 and P70-Control, the fusion (F) protein of P70-Thapsigargin virus exhibited a unique mutation at amino acid residue 104 (E104K) whereas no Thapsigargin-associated mutations were observed in HN gene. To the best of our knowledge, this is the first report describing the virus supportive role of SERCA and a rare report suggesting that viruses may acquire resistance even in the presence of an inhibitor that targets a cellular factor.